Czym była Marksowska krytyka ekonomii politycznej? - Nowak, Krzysztof (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The present paper reconstructs the peculiarities of Marx’s critique of classical political economy. The first section recalls three main intellectual sources of Marxism: Classical German Philosophy, French Utopian Socialism, and English Classical Political Economy. The second section focuses on reasons why the Marxian thought has often been considered as passé. The third part shows that many examples of downgrading or even rejecting Marx’s propositions resulted from misunderstanding of the peculiarities of his method of investigation. Finally, the paper analyses possibilities of bringing back the Marx’s critique of political economy into scientific interests, for instance, in the form of modern crisis theory.